Dampak efikasi diri akademik terhadap keterlibatan siswa pada remaja - Putri, Hanifa Ashaditya Khamila; Prasetyaningrum, Susanti (Universitas Muhammadiyah Malang, 2023)
This research aims to determine the influence of academic self-efficacy on student engagement in adolescents. The method used is quantitative research with a correlational approach, and the research subjects are 84 students, consisting of 72 high school students and 12 junior high school students. The sampling technique employed is accidental sampling. The research instrument used in this study is the academic self-efficacy scale by Fredricks. The data analysis technique used is simple linear regression. The research results show that there is an influence of academic self-efficacy on student engagement with a significance value that meets the standards and a correlation coefficient value of 0.555. It can be concluded that the higher the level of academic self-efficacy an individual possesses, the higher their student engagement. Conversely, individuals with low academic self-efficacy tend to have low student engagement as well. Keywords: Academic self-efficacy, remaja, student engagement